Ovarian Cancer Updates in Tumour Biology and Therapeutics - Ho, Gwo-Yaw; Webber, Kate (IntechOpen, 2021)
Ovarian Cancer - Updates in Tumour Biology and Therapeutics presents a review of the significant advances in the understanding and management of ovarian cancer. It covers major areas of importance in this field, incorporating new knowledge that has arisen due to the advancements in molecular techniques, understanding of ovarian cancer tumour biology, evolving role of surgery and novel therapeutics in ovarian cancer. This book brings together a collection of discoveries and opinions from specialists around the world that are relevant to this disease.